The Prevalence of Refractive Errors Using the Lea Symbols Test in Preschool Children in South Tangerang - Kosin, Abdul; Indrajanti, Mirza; Farfar, Inggrid Osya (Universitas Kristen Krida Wacana, 2025)
Preschool age is a critical phase in children's visual development. Refractive errors such as myopia, hypermetropia, and astigmatism often go undetected due to limited communication abilities in young children. Early detection is essential to prevent negative impacts on growth and learning achievement. The Lea Symbols Test is an effective visual screening method, especially for children who have not yet learned to read. Objective: This study aims to determine the prevalence and types of refractive errors in preschool children in Sawah Baru Subdistrict, South Tangerang, using the Lea Symbols Test. Method: This is a descriptive quantitative study using a survey approach. The sample consisted of 123 children aged 3–7 years from three kindergartens in the area. Visual acuity was assessed using the Lea Symbols chart, followed by subjective refraction using trial lenses. Data were analyzed univariately. Results: The findings showed that 38.2% of children had refractive errors in the right eye and 40.7% in the left eye. Myopia was the most common type (17.9%), followed by astigmatism (9.8%) and hypermetropia (8.1%). Most respondents were aged 5–6 years. The Lea Symbols Test proved effective in identifying visual acuity in early childhood. Conclusion: The prevalence of refractive errors in preschool children is relatively high, with myopia being the most common. Routine eye examinations and parental education are essential for early detection and management.